Management Information Systems - Kroenke David (Mcgraw Hill Book Company, 1989)
Preface, Foundations, Introduction to Management Information Systems, Fundamental Types of Management Information Systems, Organizations and Information Systems, Management Decision Making, Personal Management Information Systems, Personal Information Systems: Goals and Applications, Components of Personal Information Systems, Developing Personal Information Systems, Workgroup Management Information Systems, Workgroup Information Systems: Goals and Applications, Components of Workgroup Information Systems, Developing Workgroup Information Systems, Organizational Management Information Systems, Organizational Information Systems: Goals and Applications, Components of Organizational Information Systems, Developing Organizational Information Systems, Decision Support and Expert Systems, Decision Support Systems, Knowledge Representation and Expert Systems, Glossary, Index.
Preface, Foundations, Introduction to Management Information Systems, Fundamental Types of Management Information Systems, Organizations and Information Systems, Management Decision Making, Personal Management Information Systems, Personal Information Systems: Goals and Applications, Components of Personal Information Systems, Developing Personal Information Systems, Workgroup Management Information Systems, Workgroup Information Systems: Goals and Applications, Components of Workgroup Information Systems, Developing Workgroup Information Systems, Organizational Management Information Systems, Organizational Information Systems: Goals and Applications, Components of Organizational Information Systems, Developing Organizational Information Systems, Decision Support and Expert Systems, Decision Support Systems, Knowledge Representation and Expert Systems, Glossary, Index.